2022
DOI: 10.3390/molecules27144325
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Permeabilization and Antimicrobial Activity of Recombinant Defensin-d2 and Actifensin against Multidrug-Resistant Pseudomonas aeruginosa and Candida albicans

Abstract: Antimicrobial resistance requires urgent efforts towards the discovery of active antimicrobials, and the development of strategies to sustainably produce them. Defensin and defensin-like antimicrobial peptides (AMPs) are increasingly gaining pharmacological interest because of their potency against pathogens. In this study, we expressed two AMPs: defensin-d2 derived from spinach, and defensin-like actifensin from Actinomyces ruminicola. Recombinant pTXB1 plasmids carrying the target genes encoding defensin-d2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 70 publications
1
9
0
Order By: Relevance
“…We postulate that the disruption of membrane integrity or membrane permeability in the treated organism induced dysfunctional transmembrane transport, resulting in the increased leakage of ATP and accumulation of oxidative stress, which in turn altered nucleotide synthesis, affected the mitochondria, or caused DNA/RNA degradation. This correlates with our previous study that showed that both peptides induced oxidative stress in C. albicans within 1 h after exposure ( 20 ). Other studies ( 46 48 ) also reported a membrane-targeted mechanism of action of AMPs against C. albicans .…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…We postulate that the disruption of membrane integrity or membrane permeability in the treated organism induced dysfunctional transmembrane transport, resulting in the increased leakage of ATP and accumulation of oxidative stress, which in turn altered nucleotide synthesis, affected the mitochondria, or caused DNA/RNA degradation. This correlates with our previous study that showed that both peptides induced oxidative stress in C. albicans within 1 h after exposure ( 20 ). Other studies ( 46 48 ) also reported a membrane-targeted mechanism of action of AMPs against C. albicans .…”
Section: Resultssupporting
confidence: 92%
“…The method of recombinant production of defensin-d2 and actifensin was described previously ( 20 ). Briefly, an overnight culture of transformed Escherichia coli Shuffle T7 (New England Biolabs, USA) containing recombinant plasmids (pTXB1-defensin-d2 and pTXB1-actifensin) was grown in modified Terrific broth (Sigma-Aldrich, Germany) containing 100 μg/mL ampicillin.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It exhibited weak antibacterial activity against P. aeruginosa strains with MIC of 1448 μg/mL, whereas predominantly inhibited methicillin-resistant S. aureus and Candida albicans with MIC values of 23 μg/mL and 45 μg/mL. Its mechanism of anti- P. aeruginosa may be related to induce reactive oxygen species (ROS) generation, thereby destroyed cellular membrane permeability, but further molecular mechanisms were unclear ( Sugrue et al, 2020 ; Gbala et al, 2022 ). More importantly, it has been found to have a high biosafety, and it causes less than 1.5% hemolysis on mouse erythrocytes in all tested concentrations.…”
Section: Anti- Pseudomonas Aeruginosa Activity Of ...mentioning
confidence: 99%
“…Plant defensins are small cationic peptides with 5–7 kDa in size that contain multiple cysteine groups to safeguard plants against microbial invasion ( Gbala et al, 2022 ). These peptides have a wide-ranging ability to inhibit the growth of various pathogens including filamentous fungi and bacteria ( Perez-Rodriguez et al, 2022b ), we summarized the data on the inhibitory activity of several plant -derived AMPs against P. aeruginosa in Table 1 .…”
Section: Anti- Pseudomonas Aeruginosa Activity Of ...mentioning
confidence: 99%